Investigating academic-practitioner collaboration in Audiovisual Translation Studies - Tuominen, Tiina; Silvester, Hannah (Informa UK Limited, 2025)
In audiovisual translation (AVT), there has been an increase in academic research that engages with practitioners, but there is still room for more progress. In this article, we explore the findings of a study involving focus group discussions with two groups of participants; AVT academics and AVT practitioners. Through these discussions, we examined their experiences of collaborative research across the academia-practice divide, and their hopes for this kind of collaborative, engaged research in the future. The findings are examined here in relation to the concept of ‘public Translation Studies’, through which researchers are encouraged to actively engage with publics outside of academia in a dialogic fashion, in order to have an impact on the field. The findings suggest that while collaborative activities are underway between academics and practitioners, these are not always dialogic and mutually beneficial. On the other hand, among our small groups of participants, there was enthusiasm for more collaborative research, and plenty of ideas for how to make this work best. The article concludes with these important factors for successful collaboration, including the need for open communication and an equal status for those involved.